Engendering development and gender budgeting in India - Singh, Awadhesh Kumar; Singh, Atul Pratap (Madhav Books, 2017)
he issue of engendering development and women empowerment has been in the central stage with the shifting of paradigms of development and governance at the global level, particularly in India. Gender budgeting has emerged as an important instrument for gender mainstreaming and women empowerment across the globe. It has been well recognized by the policy makers and feminist economists that gender budgeting is imperative for gender equality and engendering development. Gender budgeting refers to the systematic examination of the budget programmes and policies for the impact on women. Studies show that programmes and policies are designed to improve women's economic opportunities lead to higher rates of economic growth. Gender budgeting has gained prominence in the policy circles in the recent years. Though, gender budgeting has been widely recognized tool for gender mainstreaming and engendering development, however, the analysis of gross budgetary support for women specific programmes in India demonstrates that there has been meagre share of public expenditure as against national budgets. Gross gender budget constitutes about 6 per cent of the union budget and even the share of public expenditure for women constitutes less than 4 per cent of GDP. Though, the amount of gross gender budget has shown an increasing trend however, its share in gross budgetary support has declined in the recent years. Against this view point , a national seminar on "Engendering Development and Gender Budgeting in India: Issues, Challenges and Way Forward" was organized by Center forAction and Development Research (CADRE India), under the auspices of Planning Commission, Government of India, New Delhi on October 11-12, 2014 at Vivekanand Kendra, Kanya Kumari, Tamil Nadu. The volume includes selected papers submitted in the national seminar. It highlights Gender Equality and Engendering Development, Policy Imperatives of Gender Budgeting, and Experiences and Cases of Engendering Development and Gender Budgeting. The volume will be of immense useful to the policy makers, administrators, feminine economists, and development professionals in understanding the dynamics of engendering development and budgeting in India and evolving strategies for empowerment of women .